Virtual Agent: A Determinant of Online Social Presence and Consumer Trust in Websites - Charfi, Ahmed Anis; Atif, Muhammad (International Journal of Economic Practices and Theories, 2014)
In the backdrop of rapidly changing technologically environment and rising consumer expectations, questions about the factors that make consumer more trustful of websites remain a subject interest for the researchers. One of these factors is the virtual presence of an agent on a website; a way to reduce the physical and social distance between consumers and companies. The objective of this study is to unearth the effects of such virtual agents on online social presence of websites. The study explores the effects of variables of social presence, consumer trust, online behavioral intentions, and the word-of-mouth. These formed the antecedents of the causal model which utilized SOR framework (Mehrabian and Russell , 1974; Bitner , 1992). Two well known commercial website were chosen for the study. A self-administered questionnaire was conducted on a representative sample of 481 French adults. The results showed a strong support for the relationship between virtual agents, social presence, and consumer trust. While consumer trust was found to influence online consumer behavior and word-of-mouth, thus confirming the previous research.